2017
DOI: 10.22421/1517-7130.2017v18n1p39
|View full text |Cite
|
Sign up to set email alerts
|

Análise do controle da toxoplasmose gestacional e ocular nos serviços de atenção primária da 15ªRegional de Saúde do Paraná

Abstract: Isto mostra a importância da atualização profissional e perseverança da educação continuada. PALAVRAS-CHAVE:Toxoplasmose gestacional/ocular. Profilaxia. Toxoplasma gondii. Profissionais da saúde.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Even among health professionals, insufficient knowledge about toxoplasmosis has been reported in several studies (Alvarado-Esquivel et al, 2011;da Silva et al, 2011;Efunshile et al, 2017). A survey conducted in health units, in the same geographic region of this study, showed that 83% of health professionals who attended pregnant women in prenatal care did not correctly answer what are the prophylactic measures to prevent T. gondii infection, but 100% stated that the presence of cats increases the risk of infection (Evangelista et al, 2017). People traditionally trust these professionals and they have an important role in providing information to patients, which reinforces the need for action and continued education programs on this zoonosis.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Even among health professionals, insufficient knowledge about toxoplasmosis has been reported in several studies (Alvarado-Esquivel et al, 2011;da Silva et al, 2011;Efunshile et al, 2017). A survey conducted in health units, in the same geographic region of this study, showed that 83% of health professionals who attended pregnant women in prenatal care did not correctly answer what are the prophylactic measures to prevent T. gondii infection, but 100% stated that the presence of cats increases the risk of infection (Evangelista et al, 2017). People traditionally trust these professionals and they have an important role in providing information to patients, which reinforces the need for action and continued education programs on this zoonosis.…”
Section: Discussionmentioning
confidence: 64%
“…Our toxoplasmosis research group belongs to a public university with activity in gestational and congenital toxoplasmosis diagnosis and follow-up, covering 30 municipalities with a estimate population of 750,000 inhabitants. Since 2003 educational and guidance work has been carried out on toxoplasmosis prevention among students in school grade and health professionals in diverse public and private services (Branco et al, 2012;Contiero-Toninato et al, 2014;Evangelista et al, 2017;Higa et al, 2010;Marchioro et al, 2015;A. P. Sanders et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…during gestation for IgM/IgG-negative pregnant women, high cost of complementary diagnostic methods, logistics and difficulty accessing services in different geographical regions. Throughout this study, other efforts have been developed such as an educational action between health professionals and pregnant women, adding to the support of this reference center in gestational toxoplasmosis, with the aim of increasing control of this zoonosis [30][31][32][33] . The serological IgA test was performed in a minority of cases due to restricted financial resources, which can be considered a limitation of this study, but the test indicates a correlation with the 66% of pregnant women with low IgG avidity, including cases of foetal deaths and the presence of T. gondii DNA in blood or amniotic fluid samples.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons include late prenatal evaluation, serological tests being available only twice during gestation for IgM/IgG-negative pregnant women, high cost of complementary diagnostic methods, logistics and difficulty accessing services in different geographical regions. Throughout this study, other efforts have been developed such as an educational action between health professionals and pregnant women, adding to the support of this reference center in gestational toxoplasmosis, with the aim of increasing control of this zoonosis 30 – 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Para alguns autores, a instituição da EPS enfrenta como desafios a própria sobrecarga de trabalho, além da infraestrutura deficiente e pouco apoio do sistema de saúde quanto à proteção jurídica/ inovação em relação ao fazer cotidiano. [58][59][60] No contexto do processo de trabalho do enfermeiro observam-se duas dimensões cuidativas complementares: a assistencial e a gerencial. Na primeira, o objeto de intervenção compõe-se das necessidades de cuidado de enfermagem com objetivo de prestar o cuidado integral aos indivíduos, famílias e comunidades.…”
Section: Discussionunclassified